A Review of Reading Interventions for Students With Moderate and Severe Intellectual Disabilities - Alice N. Williams, PhD, CCC-SLP
For students with moderate and severe intellectual disability (ID), reading instruction has focused on teaching sight words. However, research supports a shift in focusing instruction on reading skills such as phonemic awareness, phonics, and fluency. The purpose of this systematic literature review was to focus on the research completed with students with moderate and severe ID, discuss the reading components targeted, evidence-based practices used, treatment intensity of interventions, and measure progress toward the goal in single-case studies. Database searches from 2000 to 2022 were conducted, finding 24 studies that met inclusion criteria and quality indicators. The results indicate that research is expanding to focus on interventions including a variety of reading components for students in this population.